PREVALENCE OF WAX STOPPER IN CHILDREN IN RIO GRANDE DO NORTE - Bedaque, Henrique; Ferreira, Lidiane Maria de Brito Macedo; Clemente, Marconi Júlio Ferreira; Morais, Gabriel Maia; Cavalcante, Luiz Eduardo Queiroz (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
Introduction: Cerumen, popularly known as earwax, is a substance produced by the sebaceous and ceruminous glands of the outer two thirds of the ear canal. The presence of cerumen is usually asymptomatic, but in symptomatic patients there is an indication of appropriate therapy. Objectives: To evaluate the prevalence and associated symptoms of ear cerumen in children from a tertiary hospital. Methodology: This is an analytical, transversal and observational research, within a quantitative approach. An epidemiological study in which it is expected to obtain, by sampling, the prevalence of the entire pediatric population in the state of Rio Grande do Norte. This research was carried out with an age group, over 5 years old to under 18 years old. Results: A total of 385 children participated in the research, being 51.2% male (n=197) and 48.8% female (n=188), age ranged from 6 to 17 years, with an average 10.05. Among the total number of participants, the presence of wax was verified in 326 (84.7%), with cerumen impaction in 45 children (11.7%). Furthermore, of the total cases of total obstruction, 46.6% were bilateral. Conclusion: Cerumen impaction is a common problem observed in Brazilian children. It is evident the importance of increasing accessibility to the health service that is capable of performing otoscopy, in addition to ear lavage, in order to reduce the prevalence and impact of cerumen impaction in children in Brazil.